2008
DOI: 10.1007/s10549-008-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of antiprogestin resistance and progesterone receptor isoform ratio in acquired resistant mammary carcinomas

Abstract: To explore mechanisms related to hormone resistance, three resistant variants of the MPA mouse breast cancer tumor model with low levels of progesterone receptor (PR) isoform A (PR-A)/high PR-B expression were developed by prolonged selective pressure with antiprogestins. The resistant phenotype of one tumor line was reversed spontaneously after several consecutive passages in syngeneic BALB/c mice or by 17-beta-estradiol or tamoxifen treatment, and this reversion was significantly associated with an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
56
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 51 publications
12
56
0
Order By: Relevance
“…www.endocrinology-journals.org (Aupperlee et al 2005, Wargon et al 2008. In addition, in immunofluorescence studies, we observed that both PR isoforms were co-expressed in the same cells.…”
Section: Lanari Et Al: Mpa Breast Cancer Modelsupporting
confidence: 62%
See 4 more Smart Citations
“…www.endocrinology-journals.org (Aupperlee et al 2005, Wargon et al 2008. In addition, in immunofluorescence studies, we observed that both PR isoforms were co-expressed in the same cells.…”
Section: Lanari Et Al: Mpa Breast Cancer Modelsupporting
confidence: 62%
“…It is possible that the increased E 2 levels observed in pregnancy might be counteracting the proliferative effect of Pg. The administration of three different antiprogestins, mifepristone (RU-486), onapristone (ZK 98299) or ZK 230211 (Hoffmann & Sommer 2005), in daily s.c. doses of 6-12 mg/kg body weight, also inhibited tumor growth or induced complete tumor regressions in most of the ductal HI variants growing in BALB/c (Kordon et al 1991, Montecchia et al 1999a, Vanzulli et al 2002, Wargon et al 2008 (Lamb et al 2005b). The antiandrogens hydroxyflutamide and flutamide had no effect (Montecchia et al 1999a).…”
Section: Treatment Responsiveness and Tumor Regressionmentioning
confidence: 94%
See 3 more Smart Citations